A COMPREHENSIVE ANALYSIS OF HEALTHY LIFESTYLE, PREVENTION, AND TREATMENT (Ustozlar uchun, 2025)
A Comprehensive Analysis of Healthy Lifestyle, Prevention, and TreatmentRelevance: The high prevalence of chronic, Non-Communicable Diseases (NCDs), a major global health challenge, necessitates a paradigm shift in healthcare delivery from reactive treatment to proactive prevention. A large proportion of NCD cases are directly linked to modifiable lifestyle factors.